Preparation and Properties Study of Magnesium Potassium Phosphate-based Carbon-Solidifying Cementitious Materials - Li, Haijie; Guo, Ziru; Chen, Shiying (International Journal of Materials Science and Technology Studies, 2025)
This study systematically investigates the effects of the Mg/P ratio, water-to-binder ratio, pre-curing time, and mineral admixtures on the performance of magnesium potassium phosphate cement (MKPC) as a carbon sequestration material. The results demonstrate that an Mg/P ratio of 3:1 provides the highest compressive strength under both ambient and carbonation curing conditions, with unreacted MgO serving as an additional magnesium source during carbonation. A water-to-binder ratio of 0.25 promotes sufficient hydration and a stable pore structure, leading to enhanced mechanical properties. The incorporation of carbide slag (CCR) notably improved the carbonation rate compared to the control group, while metakaolin contributed to the formation of binding phases that refined the microstructure. Pre-curing duration significantly influenced the reaction kinetics and diffusion of CO₂, with both insufficient and excessive durations negatively affecting carbonation efficiency. The findings provide important insights into the design of high-performance MKPC-based materials for carbon capture and storage.